2004
DOI: 10.1007/s00421-004-1122-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the metabolic response to prolonged exercise with [13C]glucose ingestion

Abstract: The metabolic response to a 120-min cycling exercise with ingestion of [(13)C]glucose (3 g kg(-1)) was compared in women in the follicular phase of the cycle [ n=6; maximum rate of oxygen uptake (VO(2max)) 44.7 (2.6) ml kg(-1) min(-1)] and in men [ n=6; VO(2max) 54.2 (4.3) ml kg(-1) min(-1)] working at the same relative workload (approximately 65% VO(2max): 107 and 179 W in women and men, respectively). We hypothesized that the contribution of endogenous substrate oxidations (indirect respiratory calorimetry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
2
14
0
5
Order By: Relevance
“…1). Although this is consistent with one previous study (27) that investigated sex-related differences in fuel utilization with CHO supplementation, another study (23) has reported significantly higher rates of exogenous CHO oxidation during exercise in males compared with females during exercise (0.9 vs. 0.6 g/min, respectively). The present study and the aforementioned other two studies utilized largely similar subject groups, in terms of aerobic capacity and training status, and employed a similar relative exercise intensity, duration, and CHO feeding schedule.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1). Although this is consistent with one previous study (27) that investigated sex-related differences in fuel utilization with CHO supplementation, another study (23) has reported significantly higher rates of exogenous CHO oxidation during exercise in males compared with females during exercise (0.9 vs. 0.6 g/min, respectively). The present study and the aforementioned other two studies utilized largely similar subject groups, in terms of aerobic capacity and training status, and employed a similar relative exercise intensity, duration, and CHO feeding schedule.…”
Section: Discussionsupporting
confidence: 79%
“…Two studies have directly investigated potential sex-related differences in substrate metabolism with CHO ingestion during exercise (23,27), both using 13 C-labeled glucose ingestion to obtain measures of exogenous and endogenous CHO oxidation during exercise in men and women. However, these studies did not infuse isotopic tracers or measure plasma glucose enrichment, and therefore, estimates of the effects of CHO ingestion on glucose kinetics and the oxidation of the respective endogenous CHO sources (liver and muscle glycogen) during exercise could not be made.…”
mentioning
confidence: 99%
“…Tal fato justificaria uma possível diferença entre os sexos na recomendação de macronutrientes em esportes de longa duração. Contudo, outros autores não encontraram diferenças significativas, entre homens e mulheres, na proporção dos substratos utilizados durante o exercício [11][12][13][14][15][16][17][18][19] . Roepstorff et al 12 destacaram que a contribuição relativa de carboidratos e lipídeos como combustíveis, durante o exercício submáximo, é resultado da utilização dos diferentes carboidratos (glicose sangüínea e glicogênio muscular) e dos lipídeos (ácidos graxos de cadeia longa ligados à albumina plasmática, ácidos graxos dos triacilgliceróis presentes nas lipoproteínas de muito baixa densidade -VLDL-e ácidos graxos dos triacilgliceróis das células musculares).…”
Section: N T R O D U ç ã Ounclassified
“…O ciclo menstrual parece influenciar a utilização de carboidratos nas mulheres durante o exercício 29 , mas não altera o metabolismo de lipídeos 30 . É importante observar que a maioria dos estudos vem comparando homens e mulheres, quando estas estão na fase folicular do período menstrual (momento em que as concentrações de 17β-estradiol estão relativamente baixas) [2][3][4]7,12,13,15,20,[31][32][33][34] . As diferenças entre os sexos podem ser maiores quando as mulheres são avaliadas na fase luteal do ciclo menstrual 23 .…”
Section: N T R O D U ç ã Ounclassified
See 1 more Smart Citation